2022
DOI: 10.3389/fimmu.2022.1013049
|View full text |Cite
|
Sign up to set email alerts
|

CAPN8 involves with exhausted, inflamed, and desert immune microenvironment to influence the metastasis of thyroid cancer

Abstract: BackgroundThyroid cancer (THCA) is the most prevalent malignant disease of the endocrine system, in which 5-year survival can attain about 95%, but patients with metastasis have a poor prognosis. Very little is known about the role of CAPN8 in the metastasis of THCA. In particular, the effect of CAPN8 on the tumor immune microenvironment (TIME) and immunotherapy response is unclear.Material and methodsMultiome datasets and multiple cohorts were acquired for analysis. Firstly, the expression and the prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Numerous studies have confirmed that tumor immune cell infiltration could influence the efficacies of chemotherapy, radiotherapy, or immunotherapy as well as metastasis, such as ovarian tumor, neuroblastoma, and so on. [42][43][44][45] Our results suggested that the four TRIMs are positively correlated with CD4 + T cells and macrophages. CD4 + T cells and tumor-associated macrophages could participate in tumor development via many signaling pathways, such as the Wnt and NF-κB signaling pathways.…”
Section: Discussionmentioning
confidence: 52%
“…Numerous studies have confirmed that tumor immune cell infiltration could influence the efficacies of chemotherapy, radiotherapy, or immunotherapy as well as metastasis, such as ovarian tumor, neuroblastoma, and so on. [42][43][44][45] Our results suggested that the four TRIMs are positively correlated with CD4 + T cells and macrophages. CD4 + T cells and tumor-associated macrophages could participate in tumor development via many signaling pathways, such as the Wnt and NF-κB signaling pathways.…”
Section: Discussionmentioning
confidence: 52%
“…[70] In recent years, immunotherapy has been extensively used in cancer treatment including TC. [26,[71][72][73][74][75][76][77][78][79][80][81] In this study, papers on immunotherapy for TC were studied by using bibliometric method.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the font indicates the frequency. The top 10 keywords are: immunotherapy (232), thyroid cancer (76), radioimmunotherapy (70), immune checkpoint inhibitors (54), cancer (41), nivolumab (37), anaplastic thyroid cancer (33), prognosis (33). Figure 6B shows the thematic evolution map.…”
Section: Analysis Of Abstractmentioning
confidence: 99%
“…Our findings also warrant investigation into the role of capn8 during embryogenesis and possible implications for known craniofacial or other disorders. Recently, Capn8 has been implicated in EMT associated with cancer metastasis (Zhong, Xu et al 2022, Song, Cui et al 2024) and Xenopus capn8 was found to be required for CNCC migration (Cousin, Abbruzzese et al 2011). Together these findings support a role of capn8 in CNCC migration and craniofacial morphogenesis.…”
Section: Discussionmentioning
confidence: 99%